THE ROLE OF E-MONEY ON FOOD MSME IN MANADO CITY - Andrea Bella Tesalonika Supit; S. L. H. V. Joyce Lapian; Regina Trifena Saerang (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
Electronic money or E-money is an electronic store of monetary value on a technical device that may be widely used for making payments to entities other than the e-money issuer. Electronic money was introduced to Indonesia in 2009 and had a lot of significant effects on the country’s economy, especially on the micro, small, and medium enterprises (MSME). The goal of this study is to analyze the role that have been brought by electronic money. The research study’s sample consists of 15 informants of food MSME owner. This study uses a descriptive-qualitative approach in order to give us a detailed explanation of this phenomenon using field data. This research might be excellent references for those interested in the same topic, as well as a body of knowledge and practical implications.   Keywords: E-money, MSME